Lateralization of Cognitive Functions in Aphasia after Right Brain Damage - Ha, Ji-Wan (Yonsei University College of Medicine, 2012)
PURPOSE: The lateralization of cognitive functions in crossed aphasia in dextrals (CAD) has been explored and compared mainly with cases of aphasia with left hemisphere damage. However, comparing the neuropsychological aspects of CAD and aphasia after right brain damage in left-handers (ARL) could potentially provide more insights into the effect of a shift in the laterality of handedness or language on other cognitive organization. Thus, this case study compared two cases of CAD and one case of ARL. MATERIALS AND METHODS: The following neuropsychological measures were obtained from three aphasic patients with right brain damage (two cases of CAD and one case of ARL); language, oral and limb praxis, and nonverbal cognitive functions (visuospatial neglect and visuospatial construction). RESULTS: All three patients showed impaired visuoconstructional abilities, whereas each patient showed a different level of performances for oral and limb praxis, and visuospatial neglect. CONCLUSION: Based on the analysis of these three aphasic patients' performances, we highlighted the lateralization of language, handedness, oral and limb praxis, visuospatial neglect and visuospatial constructive ability in aphasic patients with right brain damage.